Evaluation, causes and management of acute spontaneous dizziness - Subahi, Emad A.; Alanazi, Adel Saleh; Alanazi, Laila Khaled; Alharbi, Mohammed Khalid; Shehab, Hussain Ali Bu; Alnakhli, Fares Abdullah; Tawhari, Maryam Abdullah; Alshammari, Sulaiman Mulfi; Alshahrani, Mohammed Munir; Alfaifi, Abdulmajeed Salem; Almotairi, Bandar Mohammed (International Journal Of Community Medicine And Public Health, 2022)
Although acute dizziness is a very frequent reason for admissions to emergency care, its differential diagnosis is difficult to establish due to many factors. Dizziness may mean diverse sensations such as vertigo, lightheadedness, presyncope, disequilibrium, or simply feeling unwell. The classical approach to dizziness initiates with characterizing the form of dizziness according to the belief that every kind of dizziness represents a particular underlying etiology: vertigo is vestibular, presyncope is cardiovascular, disequilibrium is neurological, and nonspecific dizziness is psychogenic or metabolic. Development of acute dizziness/vertigo unaccompanied by precipitating features occurs in patients of acute spontaneous dizziness. The dizziness/vertigo mainly presents with autonomic symptoms like imbalance, nausea, and vomiting. Dizziness/vertigo and imbalance are the commonest manifestations in vertebrobasilar ischemia, which accounts for over 20% of all ischemic strokes. It is essential to distinguish between isolated vascular vertigo from less severe disorders related to the inner ear as the treatment plan and prognosis vary among these problems. The development of diffusion-weighted magnetic resonance imaging (MRI) has improved the infarction identification in cases with vascular dizziness/vertigo, particularly from undermined posterior blood flow. Nonetheless, proper bedside neurotologic assessment which includes components such as head impulse/thrust test, head shaking nystagmus test and ocular tilt reaction test demonstrate higher sensitivity than imaging in diagnosing acute cerebrovascular accidents as an etiology of abruptly occurring vertigo lasting longer than one day, particularly in the initial 48 hours.